The development of an intervention programme to reduce whole-body vibration exposure at work induced by a change in behaviour: a study protocol - Frings-Dresen Monique HW; Hulshof Carel TJ; Tiemessen Ivo JH (BMC, 2007)
Abstract Background Whole body vibration (WBV) exposure at work is common and studies found evidence that this exposure might cause low back pain (LBP). A recent review concluded there is a lack of evidence of effective strategies to reduce WBV exposure. Most research in this field is focussed on the technical implications, although changing behaviour towards WBV exposure might be promising as well. Therefore, we developed an intervention programme to reduce WBV exposure in a population of drivers with the emphasis on a change in behaviour of driver and employer. The hypothesis is that an effective reduction in WBV exposure, in time, will lead to a reduction in LBP as WBV exposure is a proxy for an increased risk of LBP. Methods/Design The intervention programme was developed specifically for the drivers of vibrating vehicles and their employers. The intervention programme will be based on the most important determinants of WBV exposure as track conditions, driving speed, quality of the seat, etc. By increasing knowledge and skills towards changing these determinants, the attitude, social influence and self-efficacy (ASE) of both drivers and employers will be affected having an effect on the level of exposure. We used the well-known ASE model to develop an intervention programme aiming at a change or the intention to change behaviour towards WBV exposure. The developed programme consists of: individual health surveillance, an information brochure, an informative presentation and a report of the performed field measurements. Discussion The study protocol described is advantageous as the intervention program actively tries to change behaviour towards WBV exposure. The near future will show if this intervention program is effective by showing a decrease in WBV exposure.